1984
DOI: 10.1259/0007-1285-57-676-323
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine treatment of metastatic thyroid carcinoma: the Royal Marsden Hospital experience

Abstract: The case records of 235 patients who were treated for differentiated thyroid cancer between 1949 and 1981 were reviewed. Forty-two (18%) had distant metastatic spread outside the neck and received radioiodine (131I) therapy. In cases where the distant spread was confined to the lungs, 54% of patients were alive, free of disease, 10 years after 131I treatment was started. By contrast, no patient with skeletal involvement has survived for 10 years and only one for five years after treatment. A variety of cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
3
7

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(86 citation statements)
references
References 8 publications
3
73
3
7
Order By: Relevance
“…The levels above and below the vertebrectomy site were counted as parts of the anterior column construct when plating, Steinmann pins, or chest tube insertion were involved. Fourteen patients did not require posterolateral stabilization; of those who did, the median length of the construct was 6 vertebral levels (range [3][4][5][6][7][8][9][10][11][12][13][14]. Two patients underwent lumbopelvic or lumbosacropelvic fixation; in these instances, the sacrum or pelvis was treated as 1 level.…”
Section: Operative Datamentioning
confidence: 99%
“…The levels above and below the vertebrectomy site were counted as parts of the anterior column construct when plating, Steinmann pins, or chest tube insertion were involved. Fourteen patients did not require posterolateral stabilization; of those who did, the median length of the construct was 6 vertebral levels (range [3][4][5][6][7][8][9][10][11][12][13][14]. Two patients underwent lumbopelvic or lumbosacropelvic fixation; in these instances, the sacrum or pelvis was treated as 1 level.…”
Section: Operative Datamentioning
confidence: 99%
“…However, studies using radioactive iodine therapy for bone metastases have shown that the metastases are generally resistant to 131 I and may require other approaches [14]. Brown et al [15] reported no 10-year survivors in a group of patients with bone metastases treated with 131 I, but a 54 % 10-year survival rate for patients with lung metastases. Moreover, a previous retrospective study evaluated the therapeutic outcome, total administered radioiodine activity, and side effects in 107 patients with initial bone metastases [16].…”
Section: Discussionmentioning
confidence: 99%
“…These patients had also received high cumulative doses of '3'I (Schlumberger et al, 1996). Hence, more investigations are necessary to assess the respective role of high activities of 131I and of external beam radiotherapy (Brown et al, 1984;Edmonds et al, 1986;Brinker et al, 1987). This result is strengthened by the fact that the dose from3'1I delivered to bone marrow could be higher in thyroid cancer patients than estimated in ICRP tables for euthyroid subjects (ICRP, 1988), because the hypothyroid status of these patients decreases the renal clearance of 1311, thus increasing the whole body retention of 1311 and the mean whole body radiation dose.…”
Section: Discussionmentioning
confidence: 99%